2016
DOI: 10.1016/j.marenvres.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic evaluation of the American oyster, Crassostrea virginica, deployed during the Deepwater Horizon oil spill: Evidence of an active hydrocarbon response pathway

Abstract: Estuarine organisms were impacted by the Deepwater Horizon oil spill which released ∼5 million barrels of crude oil into the Gulf of Mexico in the spring and summer of 2010. Crassostrea virginica, the American oyster, is a keystone species in these coastal estuaries and is routinely used for environmental monitoring purposes. However, very little is known about their cellular and molecular responses to hydrocarbon exposure. In response to the spill, a monitoring program was initiated by deploying hatchery-rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 62 publications
4
10
0
Order By: Relevance
“…Energy intensive house-keeping functions such as DNA replication are down-regulated while genes involved in general detoxification pathways and stress response are up-regulated. This response is consistent with other studies on sponges (Guzman and Conaco, 2016) and other aquatic organisms (Leveelahti et al, 2011;Jenny et al, 2016) exposed to chemical and thermal stressors or nutrient deprivation (Fan et al, 2020).…”
Section: Gene Expressionsupporting
confidence: 91%
See 2 more Smart Citations
“…Energy intensive house-keeping functions such as DNA replication are down-regulated while genes involved in general detoxification pathways and stress response are up-regulated. This response is consistent with other studies on sponges (Guzman and Conaco, 2016) and other aquatic organisms (Leveelahti et al, 2011;Jenny et al, 2016) exposed to chemical and thermal stressors or nutrient deprivation (Fan et al, 2020).…”
Section: Gene Expressionsupporting
confidence: 91%
“…Cellular response to hydrocarbon exposure is often mediated through the aryl hydrocarbon receptor (AHR) pathway (Puga et al, 2002;Jenny et al, 2016). Target of the AHR pathway include both Phase I and Phase II detoxification genes and may also cause changes to the cell cycle (Puga et al, 2002).…”
Section: Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase I biotransformation of PAHs is mostly mediated by CYP1A enzymes in vertebrates, whereas other CYP enzymes than the CYP1 subfamily seem to be involved in PAH biotransformation in marine invertebrates (Livingstone 1993). Only a few studies showed the existence of the aryl hydrocarbon receptor (AHR) transcription factor in marine invertebrates and suggested that the expression of Phase I enzymes through AHR in response to hydrocarbon exposure might be tissue-specific in bivalves (Skarphéðinsdóttir et al 2003;Jenny et al 2016). Additionally, relatively large differences in dominating Phase II biotransformation pathways between invertebrates could yield different PAH metabolite patterns.…”
Section: Pyrene Metabolitesmentioning
confidence: 99%
“…Moreover, an ASTM (American Society for Testing and Materials) guideline for field bivalve testing exists (ASTM, 2013). However, these monitoring studies use transplanted adult (rarely juvenile) oysters (Cao and Wang, 2016;Clara Rebouças Do Amaral et al, 2005;Hédouin et al, 2011;Jenny et al, 2016;Lee and Birch, 2016) or mussels (Benedicto et al, 2011;Brooks et al, 2012;Cappello et al, 2015;Devier et al, 2005;Haynes et al, 1995;Lehtonen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%